Partnership for productive development of biosimilar products: perspectives of access to biological products in the Brazilian market - Scheinberg,Morton Aaron (2018)
ABSTRACT The manufacturing process for biological products is complex, expensive and critical to the final product, with an impact on their efficacy and safety. They have been increasingly used to treat several diseases, and account for approximately 50% of the yearly budget for the Brazilian public health system. As the patents of biological products expire, several biosimilars are developed. However, there are concerns regarding their efficacy and safety; therefore, the regulatory agencies establish rules to approve and monitor these products. In Brazil, partnership programs between national government-owned companies and private technology holders have been implemented, aiming at knowledge sharing, capacity-building and technological transfer. Such partnerships locally promote manufacturing of these strategic drugs at reduced costs to the public health system. These agreements offer mutual advantages to both the government and patent holders: for the former, a biotechnological development flow is established and enables potential cost reduction and self-sufficient production; whereas for the latter, exclusive sales of the product are ensured during technological transfer, for a fixed period.